Local Delivery of Antibiotics in the Context of Chronic Diabetic Foot Infection with Bony Involvement: A Case Series of 102 Patients. Issue 4 (16th October 2019) - Widnall, James; Harvey, David; Evans, Paul; Jackson, Gillian; Platt, Simon
Category: Diabetes Introduction/Purpose: Diabetic foot infection (DFI) is a devastating condition which poses risk to both life and limb. Treatment principles revolve around surgical debridement, dead space management, delivery of both local and systemic antibiotics and soft tissue cover. Dead space management and local antibiotic delivery can be achieved simultaneously by using an antibiotic loaded bone substitute. We report our retrospective case series of patients treated with surgical management involving local antibiotic delivery via calcium sulphate bone substitute (Stimulan™; Biocomposites, Keele, UK). Methods: All patients between January 2015 and June 2018 with DFI and proven bony involvement presenting to our university teaching hospital were treated via our extensive MDT approach. A total of 102 patients were included. Surgical debridement was performed along with simultaneous insertion of 10 ml calcium sulphate with 1 g vancomycin and 240 mg gentamycin. Outcome was classified as resolved, requiring prolonged treatment from other medical (endocrinologist) or surgical (plastic surgery, limb reconstruction) services or salvage surgery in the form of proximal amputation. Results: 45.1% of patients had a partial amputation at the index surgery. 52% had bony debridement and just 2.9% had soft tissue debridement in conjunction with calcium sulphate insertion. The surgical wound was primarily closed in 56.8% of patients. 7 patients had delayed wound closure and 36.2% of patients healed via secondary intention. 74 patients (72.5%) had resolution of their DFI with bony involvement following surgical intervention. 21 (20.6%) patients needed further treatment from allied specialties. 7 (6.9%) patients required salvage surgery in the form of a below knee amputation. There was no correlation between either closure type (2 p-value 0.75) or index surgery type and outcome (2 p-value 0.64). Conclusion: DFI is a difficult clinical scenario to treat effectively. An MDT approach is undoubtedly key to a good outcome. We believe that the use of calcium sulphate can be a useful adjunct at the time of surgical debridement to aid in both dead space management and allow local antibiotic delivery.